Comparison between clinical and ultrasonographic findings in cases of periportal fibrosis in an endemic area for schistosomiasis mansoni in Brazil Comparação entre achados clínicos e ultrassonográficos no diagnóstico da fibrose periportal em uma área endêmica de esquistossomose no Brasil - Aluízio Prata; Raiza Ruiz-Guevara; Carlos Mauricio de Figueiredo Antunes; Carolina Coimbra Marinho; Leonardo Campos Queiroz; Izabela Voieta; José Roberto Lambertucci (Revista da Sociedade Brasileira de Medicina Tropical, 2010)
INTRODUCTION: Abdominal palpation and ultrasound findings among patients from an endemic area for schistosomiasis in Brazil who had been followed up for 27 years were compared. METHODS: In 2004, 411 patients from Brejo do Espírito Santo, in the State of Bahia, were selected for the present investigation after giving their written informed consent. Based on clinical data, they were divided into three groups: 41 patients with evidence of liver fibrosis in 2004 (Group 1); 102 patients with evidence of liver fibrosis in the past (1976-1989) but not in 2004 (Group 2); and 268 patients without evidence of liver fibrosis at any time during the 27-year follow-up (Group 3). All of the patients underwent abdominal ultrasound in which the examiner did not know the result from the clinical examination. The data were stored in a database. RESULTS: The prevalence of periportal fibrosis on ultrasound was 82.9%, 56.9% and 13.4% in Groups 1, 2 and 3, respectively. In the presence of hard, nodular liver or prominent left lobe and a hard palpable spleen, ultrasound revealed periportal fibrosis in 70.9%. However, periportal fibrosis was diagnosed using ultrasound in 25.4% of the patients in the absence of clinical evidence of liver involvement. Thus, ultrasound diagnosed periportal fibrosis 3.1 times more frequently than clinical examination did. CONCLUSIONS: Although clinical examination is important in evaluating morbidity due to Manson's schistosomiasis in endemic areas, ultrasound is more accurate in diagnosing liver involvement and periportal fibrosis. INTRODUÇÃO: Neste estudo, se comparou os achados da palpação abdominal e do ultrassom em pacientes de área endêmica de esquistossomose que foram acompanhados por 27 anos no Brasil. MÉTODOS: Em 2004, 411 pacientes de Brejo do Espírito Santo, no estado da Bahia, após consentimento informado e por escrito foram selecionados para o presente estudo. Baseando-se no exame clínico eles foram divididos em 3 grupos: 41 (Grupo 1) com evidência de fibrose hepática no ano de 2004; 102 (Grupo ...